Unveiling the mechanism of melatonin impacts on maize seedling growth: sugar metabolism as a case - Zhao, Hongbo; Su, Tao; Huo, Liuqing; Wei, Hongbin; Jiang, Yang; Xu, Lingfei; Ma, Fengwang (Journal of pineal research, 2015)
Melatonin regulates growth in many plants; however, the mechanism remains unclear. In this study, exogenous melatonin feeding resulted in both promotional (≤10 μm) and inhibitory (≥100 μm) effects on maize seedling growth. Initial analyses suggested positive correlations between the amount of melatonin and sucrose synthesis and hydrolysis-related gene expression, enzyme activities, and sucrose metabolites. However, assays of photosynthetic rate, hexokinase (HxK) activity, expression of photosynthetic marker genes, and HxK-related genes showed opposite effects under 10 μm (positive) and 100 μm (negative) melatonin treatments. Similarly, 10 μm melatonin accelerated starch catabolism at night, whereas 100 μm melatonin significantly decreased this process and led to starch accumulation in photosynthetic tissues. Furthermore, expression analysis of genes related to sucrose phloem loading resulted in a slight upregulation of sucrose transporters (SUT1 and SUT2) when seedlings were induced with 10 μm melatonin, while treatment with 100 μm melatonin resulted in significant downregulation of these sucrose transporter genes (SUT1 and SUT2), as well as tie-dyed2 (Tdy2) and sucrose export defective 1. Taken together, these results suggest that low doses of melatonin benefit maize seedling growth by promoting sugar metabolism, photosynthesis, and sucrose phloem loading. Conversely, high doses of melatonin inhibit seedling growth by inducing the excessive accumulation of sucrose, hexose and starch, suppressing photosynthesis and sucrose phloem loading.